Mid-term outcomes among West African HIV-infected children initiating first line lopinavir-based antiretroviral therapy before two years of age : feasibility, tolerance, adherence, effectiveness, simplification - (:unkn) unknown (My University, 2017)
The WHO 2010 guidelines recommended to treat all HIV-infected children < 2 years of age, and for those < three years, a lopinavir/ritonavir (LPV/r) based antiretroviraltherapy (ART) is recommended. But, less is known about its field implementation and effectiveness in West Africa (WA) settings. Our objective was to document the midterm (25 months) outcomes of the early ART (EART) initiation in West-African HIVinfected infants before the age of two years and its correlates. We assessed thefeasibility of EART; to assess its clinical, immunological, virological outcomes and its tolerance; to assess its simplification by switching to a protease inhibitor-sparingtherapy based on efavirenz (EFV) in virologically suppressed infants; and to describe the HIV drug resistance profile in those with virological failure. Our findings show thatin WA settings, EART is feasible, but access to early infant HIV diagnosis and EART remains too late with a high rate of competing mortality before and after ART initiation.Despite this delay, LPV/r-based EART is well tolerate and effective in mid-term with viral suppression reaching 78% 12-month and 74% at-24-months. In virologically suppressed children, LPV/r-based ART could be simplify with EFV-based ART, but this simplification strategy needs implementation in adherent infants with a closely viralload monitoring. In children with virological failure, resistance analyses highlighted a high frequency of nucleoside and non-nucleoside reverse transcriptase inhibitorsresistance mutations. It is urgent to develop innovative interventions to improve early HIV-infected infant diagnosis and EART and to strengthen lifelong treatment adherence in WA.
Keywords: African Research